**angle A=X, angle B=3X-2, angle C=Y (Given)**

**Since it is given,**

** angleC-angleB**

**⇒Y-(3X-2)=9**

**⇒Y-3X+2=9**

**We can find out the value of Y from the above formed equation,**

**⇒Y-3X=9-2**

**⇒Y=7+3X······························ (i)**

**Since we know all the angles of the triangles sum up to 180,**

**We can form the equation**

**angleA+angleB+angleC=180**

**Now substituting the values of the angles,**

**We get,**

**⇒X+3X-2+Y=180**

**We can replace the value of Y from equation (i),**

**we get,**

**⇒X+3X-2+7+3X=180**

**⇒7X+5=180**

**⇒7X=180-5**

**⇒X=175/7**

**⇒X=25**

**Since we got the value of X we can find out the values of other angles,**

**angle A= X =25**

**angle B= 3X-2 =3*25-2 =73**

**angle C= Y =(7X+3) = 82**

**Hence, the angles are**

**angle A=25, angle B=73, angle C=82**